Enhancing Development through Cooperatives: September 2014 Workshop (Addis Ababa, Ethiopia) - International Center for Tropical Agriculture (2014)
The Enhancing Development through Cooperatives workshop was held from September 1 to 3 in Addis Ababa, Ethiopia. The event was hosted and sponsored by the US Overseas Cooperative Development Council (OCDC), International Center for Tropical Agriculture (CIAT), International Food Policy Research